Can subjective comfort be used as a measure of plantar pressure in football boots? - Okholm Kryger, K.; Jarratt, V.; Mitchell, S.; Forrester, S. (Journal of Sports Sciences, 2017)
Comfort has been shown to be the most desired football boot feature by players. Previous studies have shown discomfort to be related to increased plantar pressures for running shoes which, in some foot regions, has been suggested to be a causative factor in overuse injuries. This study examined the correlation between subjective comfort data and objective plantar pressure for football boots during football-specific drills. Eight male university football players were tested. Plantar pressure data were collected during four football-specific movements for each of three different football boots. The global and local peak pressures based on a nine-sectioned foot map were compared to subjective comfort measures recorded using a visual analogue scale for global discomfort and a discomfort foot map for local discomfort. A weak (rs = -0.126) yet significant (P < 0.05) correlation was shown between the peak plantar pressure experienced and the visual analogue scale rated comfort. The model only significantly predicted (P > 0.001) the outcome for two (medial and lateral forefoot) of the nine foot regions. Subjective comfort data is therefore not a reliable measure of increased plantar pressures for any foot region. The use of plantar pressure measures is therefore needed to optimise injury prevention when designing studded footwear.